The implications of indirect evidence regarding the military pottery production in Buciumi (Dacia Porolissensis) and the question of ‘legionary ware’ - Petruţ, Dávid (Rei Cretariae Romanae Fautorum Acta, 2017)
The long-debated issue of supply is crucial for our understanding of the way in which the Roman army functioned as well as for the everyday life of the troops. Supply can be understood as the conjunction of local production and the import of various goods. The problem of military pottery production in Dacia has so far been largely neglected by researchers in Roman archaeology. Indeed, clear connections between production sites associated with military bases, i.e. pottery workshops situated in the vicus, and the forts they were meant to supply, are yet to be established. Due to this general shortcoming we are forced to rely to a great extent on ‘indirect evidence’ for the assessment of local military pottery production. The notion of indirect evidence in this case refers mainly to particular categories of the material culture, such as implements and tools used in pottery production, but also wasters and other discarded by-products linked to the process of manufacture. Evidence derived from the analysis of certain traits and patterns in the pottery assemblages which might indicate the parameters of local production are equally significant. The underlying principle behind this approach is based on the assumption that the overwhelming majority of the pottery assemblages were produced in the immediate vicinity of the fort, i.e. in the vicus.